KONTRIBUSI METODE PEMBELAJARAN STRUCTURED DYADIC METHODS DALAM PENINGKATAN HASIL BELAJAR SISWA PADA PELAJARAN ILMU PENGETAHUAN ALAM - Imam Sofi’i; Indah Pertiwi (PIKTORIAL : Journal of Humanities, 2019)
ABSTRACT This study aims to improve science learning outcomes through the Structured Dyadic Method in class VIII students in MTs. Miftahul Falah Kayen 2017/2018 Academic Year. The structured dyadic method is a method in which students pair up, one student acts as a teacher and one student acts as a student. By using a structured dyadic method students can be active and foster curiosity about the ongoing learning material. The research method used for the learning process that occurs is classroom action research (CAR), this study uses cycle II (3 meetings). Each cycle consists of stages of planning, implementation, observation and reflection. The research instrument used consisted of tests, observation guidelines, blank field notes and documentation. The research subjects were 32 class VIII students. The first cycle of evaluation of students who have not yet reached KKM is 11 students, with a percentage of 32.21 percent, while in cycle II students who have not yet reached KKM are reduced to 2 students, with a percentage of 7.99 percent. In the first cycle the students who reached KKM were 28 students with a percentage of 70.80 percent, while in the second cycle students who achieved KKM increased to 92.10 percent with an overall score of 79.71 students overall. Keywords: Structured Dyadic, study method, study evaluating